Symbol In Edgar Allan Poe’s Selected Short Stories And Their Pedagogical Implication: A Semiotic Perspective - Arinfandira Ramadhanti, Lalu Muhaimi, Nur Ahmadi (Jurnal Ilmiah Profesi Pendidikan, 2019)
Abstract : The main objectives of this study are to identify the symbols which are contextually attached to certain words and phrases; to analyze the contextual meaning of the symbols; and to describe the pedagogical implications of the uses of those symbols to the practices of teaching English as a foreign language (TEFL). These all are conducted by following Pierce’s triadic theory. The sources of the data of this study are some carefully selected short stories written by Edgar Allan Poe. Descriptive qualitative method is used to collect the data which are then analysed and presented explanatorily. The results of the analysis of the data suggest that there are six symbols which are contextually attached to words and phrases in The Masque of Red Death, three symbols in The Pit and Pendulum, and three symbols in The Black Cat. Those symbols carry important pedagogical implications to the teaching of English as a foreign language. This implies that teachers of English may use these short stories and their symbols to teach English vocabulary in reading section by using flashcard, and by which they can conclude the learning section by presenting the moral values in the short stories.Keywords : Symbols, Semiotic